2011
DOI: 10.1080/09515070.2011.634266
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness in response to cultural microaggressions

Abstract: This study investigated prevalence and impact of cultural microaggressions among adults. When participants were asked to describe a time when they had been wronged by another person, approximately 7% identified a cultural microaggression. Adults who experienced a cultural microaggression reported significant levels of distress and moderate levels of unforgiveness (revenge and avoidance) toward the perpetrator. Victims also reported moderate levels of forgiveness about the event. There were no significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Our review found that perceived psychological distress in ethnic and racial minority groups (e.g., anxiety, diminished self-esteem, diminished self-efficacy, etc.) as the result of experiencing racial microaggressions has been documented in several settings, namely therapy (Constantine 2007; Crawford 2011; Morton 2011; Owen et al 2011; Schoulte et al 2011; Sue et al 2008a, b, c), clinical supervision (Barnes 2011; Beaumont 2010; Constantine and Sue 2007), academia (Cartwright et al 2009; Constantine et al 2008; Sue et al 2008, 2009, 2011), university classrooms and environment (Blume et al 2012; Gomez et al 2011; Granger 2011; Grier-Reed 2010; Robinson 2011; Sauceda 2010; Smith et al 2011; Sue and Constantine 2007; Sue et al 2009, 2010; Torres et al 2010; Yasso et al 2009), and the community (Burdsey 2011; De Oliveira Braga Lopez 2011; Huber 2011; Nadal 2008a; Nadal et al 2011b; Rivera et al 2010; Sue et al 2009; Wang et al 2011). However, only one study to date has explicitly explored the long-term effects of experiencing racial microaggressions (Torres et al 2010), and questions still remain regarding the cumulative effect of racial microaggressions across the lifespan.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…Our review found that perceived psychological distress in ethnic and racial minority groups (e.g., anxiety, diminished self-esteem, diminished self-efficacy, etc.) as the result of experiencing racial microaggressions has been documented in several settings, namely therapy (Constantine 2007; Crawford 2011; Morton 2011; Owen et al 2011; Schoulte et al 2011; Sue et al 2008a, b, c), clinical supervision (Barnes 2011; Beaumont 2010; Constantine and Sue 2007), academia (Cartwright et al 2009; Constantine et al 2008; Sue et al 2008, 2009, 2011), university classrooms and environment (Blume et al 2012; Gomez et al 2011; Granger 2011; Grier-Reed 2010; Robinson 2011; Sauceda 2010; Smith et al 2011; Sue and Constantine 2007; Sue et al 2009, 2010; Torres et al 2010; Yasso et al 2009), and the community (Burdsey 2011; De Oliveira Braga Lopez 2011; Huber 2011; Nadal 2008a; Nadal et al 2011b; Rivera et al 2010; Sue et al 2009; Wang et al 2011). However, only one study to date has explicitly explored the long-term effects of experiencing racial microaggressions (Torres et al 2010), and questions still remain regarding the cumulative effect of racial microaggressions across the lifespan.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…Racial and ethnic microaggressions have been associated with psychological distress, such as anger, anxiety, confusion, and contempt (e.g., Blume, Lovato, Thyken, & Denny, 2012;Mercer, Zeigler-Hill, Hayes, & Wallace, 2011;Schoulte, Schultz, & Altmaier, 2011;Wang, Leu, & Shoda, 2011). Many racial and ethnic minority (REM) individuals experience microaggressions in ev eryday life, and unfortunately they also can be experienced during therapy.…”
mentioning
confidence: 99%
“…Past research has found a significant relationship between ethnic discrimination and increased traumatic stress symptoms among Latinos (Flores et al, 2010;Pole, Best, Metzler, & Marmar, 2005). Furthermore, individuals who reported experiencing ethnic microaggressions have also indicated elevated intrusive, avoidance, and hyperarousal symptoms (Schoulte et al, 2011). …”
mentioning
confidence: 99%